2004
DOI: 10.1007/s10344-003-0032-x
|View full text |Cite
|
Sign up to set email alerts
|

Helminth parasites of the Eurasian badger ( Meles meles L.) in the Basque Country (Spain)

Abstract: The helminthological study of 26 Eurasian badgers (Meles meles L.) in the Basque Country (northern Spain) revealed the presence of two trematode (Euryhelmis squamula and Brachylaima sp.), three cestode (Atriotaenia incisa, Mesocestoides sp. and Taenia sp.) and five nematode (Aonchotheca putorii, Physaloptera sp., Molineus patens, Uncinaria criniformis and Strongyloides sp.) species. All 15 individuals analysed for Trichinella sp. were negative. The coprological analysis (flotation and migration) revealed the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
2
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 23 publications
(23 reference statements)
2
20
2
3
Order By: Relevance
“…Furthermore, it was possible to identify adults of M. muris in the badger faeces analysed. The overall helminth prevalence (62%) was low when compared with the studies of Torres et al (2001) and Millán et al (2004) in which values of 86 and 100% were found, respectively. Millán et al (2004) reported data from both necropsies and faecal analysis, and it was apparent that helminth prevalences obtained by faecal analysis were lower (e.g.…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…Furthermore, it was possible to identify adults of M. muris in the badger faeces analysed. The overall helminth prevalence (62%) was low when compared with the studies of Torres et al (2001) and Millán et al (2004) in which values of 86 and 100% were found, respectively. Millán et al (2004) reported data from both necropsies and faecal analysis, and it was apparent that helminth prevalences obtained by faecal analysis were lower (e.g.…”
Section: Discussioncontrasting
confidence: 50%
“…Nevertheless, all helminthological data from the Iberian Peninsula published in previous studies based on necropsies (Miquel 1993;Torres et al 1996Torres et al , 2001Millán et al 2004) indicate that, regarding the genera Atriotaenia, Mastophorus, Molineus and Uncinaria, only the species reported here were present. Moreover, it is reasonable to consider a biogeographical continuity within the Iberian Peninsula.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…It has been stated that the differences between badger's helminthological fauna may result from the badgers diet, abiotic factors and biocenosis present in each biogeographic area (Brglez 1988, Torres et al 2001. However, none of examined badger carcasses obtained in the Italian Alps, Finland and Spain were infected with Trichinella nematode (Oivanen et al 2002, Millan et al 2004, Balestrieri et al 2006. The absence of Trichinella spp.…”
Section: Trichinella Britovi Marten Badger Pcr Polandmentioning
confidence: 99%